Medios de cultivo para enraizamiento in vitro de Ananas comosus L. Merrill var. Roja Trujillana en Trujillo, La Libertad - Ferrer De La Cruz, Martin Ronald (2023)
This thesis work aimed to evaluate the effect of different culture media for the in vitro rooting of Ananas comosus L. Merrill var. Trujillan red, in order to compare and determine the most effective culture medium in rooting seedlings in vitro of Ananas comosus L. Merrill var. Trujillan red. It was carried out at the Biotechnology Laboratory facilities of the Faculty of Agricultural Sciences, at the National University of Trujillo, which provided in vitro seedlings of pineapple var. Trujillan red. A randomized complete design was used, with 16 treatments including the control, which were made up of different concentrations of the culture medium and of indolbutyric acid (IBA). The results determined that the most effective means of rooting seedlings in vitro of Ananas comosus L. Merrill var. Trujillan red, was treatment 9 with a concentration of MS salts at 95%, distilled water at 5% and indolbutyric acid at 0.08 ppm, since with this treatment it was possible to obtain a greater number of roots (30.16 as a general average) compared to the other treatments, considering the number of roots as the main factor that demonstrates the rooting of a seedling in vitro. The rooting rate was 1.01, determined by the average number of roots of treatment 9 within 30 days of the experiment